2015
DOI: 10.1002/ps.4037
|View full text |Cite
|
Sign up to set email alerts
|

Soil ecotoxicity assessment of glyphosate use under field conditions: microbial activity and community structure of Eubacteria and ammonia‐oxidising bacteria

Abstract: The absence of negative effects on soil microbial communities in this study suggests that glyphosate use at recommended rates poses low risk to the microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Even after long-term glyphosate use in no-till systems, only minor changes were detected in microbial communities of the wheat rhizosphere (Lupwayi et al, 2020), even though significant negative effects recently were observed for fungi (Vázquez et al, 2021). However, the methods used to study microbial communities in soil were mostly restricted to those measuring general microbial community structure, diversity, biomass or activity so that only minor or no effects were found (Allegrini et al, 2015;Banks et al, 2014;Bottrill et al, 2020;Lupwayi et al, 2020;Zabaloy et al, 2016), probably due to the great diversity and compensatory ability of microorganisms within such large groupings.…”
Section: Effects On Microorganisms In Bulk Soil Rhizosphere and Plantsmentioning
confidence: 99%
“…Even after long-term glyphosate use in no-till systems, only minor changes were detected in microbial communities of the wheat rhizosphere (Lupwayi et al, 2020), even though significant negative effects recently were observed for fungi (Vázquez et al, 2021). However, the methods used to study microbial communities in soil were mostly restricted to those measuring general microbial community structure, diversity, biomass or activity so that only minor or no effects were found (Allegrini et al, 2015;Banks et al, 2014;Bottrill et al, 2020;Lupwayi et al, 2020;Zabaloy et al, 2016), probably due to the great diversity and compensatory ability of microorganisms within such large groupings.…”
Section: Effects On Microorganisms In Bulk Soil Rhizosphere and Plantsmentioning
confidence: 99%
“…To avoid introducing errors (mainly related to an unknown number of operons per cell), we analyzed the copy numbers (Ouyang et al, 2016;Morrison et al, 2017); no attempt was made to convert these copies into cell numbers. The amplification program for AOB and AOA as well as the PCR master mix volumes and reaction setup were previously reported by Zabaloy et al (2016) and Zabaloy et al (2017), respectively. All amplifications, baseline corrections, melting curve analysis, and standard curve assessments were conducted in ABI 7500 Real− Time System and its associated software (7500 Software v2.0.3, Applied Biosystems, Foster City, CA).…”
Section: Quantitative Pcr Of Amoa Genementioning
confidence: 99%
“…Because some taxa are glyphosate sensitive, whereas others are insensitive or may benefit from it as a nutrient source, glyphosate is likely to have negative, neutral, or positive effects on soil microbial populations and to modify the microbiomes of crop plants. Consequently, it is not surprising that studies on the effects of glyphosate on microbial populations have yielded conflicting evidence, suggesting detrimental effects (9)(10)(11)(18)(19)(20), minimal or no effects (21)(22)(23)(24)(25)(26)(27), or stimulatory effects (23,(28)(29)(30)(31) on bacterial abundance, activity, and diversity.…”
mentioning
confidence: 99%